Brain Metastasis in Triple-Negative Breast Cancer - Bustamante, E (2024)
Background. Breast cancer is an important cause of cancer-related death in women worldwide and represents the second most frequent cause of brain metastases after lung cancer. The aim of this study was to determine the characteristics and outcomes of triple-negative breast cancer (TNBC) patients with brain metastasis (BM). Methods. We retrospectively reviewed a cohort of patients diagnosed with TNBC at the "Instituto Nacional de Enfermedades Neoplasicas"(period 2000-2014) to evaluate patients who developed BM. Survival rates were assessed by the Kaplan-Meier method, and prognostic factors were identified with the Cox regression analysis. Results. Of a total of 2007 TNBC patients, 193 (9.62%) developed BM. Of these, 169 stages I-III patients with a median age of 45 years (range:21-78) were included. The stage in this cohort was 4 (2.4%) clinical stage (CS) I, 23 (13.6%) with CS II and 142 (84.0%) with CS III. Most of these patients presented ECOG ≥2 (68.6%). The most common symptom was headache (74.0%), followed by nausea-vomiting (46.7%). Imaging showed that 80 patients (53.0%) had ≥1 metastatic brain lesion. Regarding the treatment of BM in this cohort, 132 patients (84.6%) received radiotherapy (RT), 2 (1.5%) surgery, and 6 (4.5%) surgery plus RT. The overall survival (OS) rate of BM was 59.8%, 37.3%, and 15.0% at 3, 6, and 12 months, respectively. A multivariate analysis showed RT to be the only factor with a positive impact on the OS of BM (hazard ratio (HR) = 0.48, 95% confidence interval (CI):0.30-0.77, and p=0.002), while ECOG ≥2 was associated with a worse OS (HR = 1.69, 95%CI:1.15-2.48, and p=0.007). Conclusion. Despite the poor prognosis of TNBC patients who develop BM, RT showed a benefit in OS rates, while ECOG ≥2 was the only prognostic factor associated with a worse OS. These results may be useful for multidisciplinary teams for treatment planning in patients with TNBC and BM.